2016
DOI: 10.2217/nnm.16.5
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Nanoparticle Size on In Vivo Pharmacokinetics and Cellular Interaction

Abstract: Nanoparticle-based technologies offer exciting new approaches to disease diagnostics and therapeutics. To take advantage of unique properties of nanoscale materials and structures, the size, shape and/or surface chemistry of nanoparticles need to be optimized, allowing their functionalities to be tailored for different biomedical applications. Here we review the effects of nanoparticle size on cellular interaction and in vivo pharmacokinetics, including cellular uptake, biodistribution and circulation half-lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
886
3
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,396 publications
(1,006 citation statements)
references
References 96 publications
22
886
3
3
Order By: Relevance
“…Studies have shown that the cytotoxicity of the drug was inversely proportional to the size of the liposomes . Size of the nanoparticles is crucial for internalization into cells and a size range between 10–60 nm in diameter is reported be ideal for endocytosis . Additionally, a protein corona on the surface of the nanoparticle enhances the endocytosis of the particles into cells with the help of various receptor ligand interactions .…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that the cytotoxicity of the drug was inversely proportional to the size of the liposomes . Size of the nanoparticles is crucial for internalization into cells and a size range between 10–60 nm in diameter is reported be ideal for endocytosis . Additionally, a protein corona on the surface of the nanoparticle enhances the endocytosis of the particles into cells with the help of various receptor ligand interactions .…”
Section: Resultsmentioning
confidence: 99%
“…These results indicated that the developed nanoparticulate system could be suitable for biological purposes. In general, slightly negatively charged nanoparticles have demonstrated excellent cellular uptake, reduced phagocytosis, minimization of nonspecific interactions, etc …”
Section: Resultsmentioning
confidence: 99%
“…It was previously reported that nanoparticle size affected the biodistribution of nanoparticles and nanoparticles with diameters larger than 200 nm were prone to activate the complement system, be rapidly removed from the blood stream, and accumulate in the liver and spleen 32 . However, PEGylation of nanoparticles, even >500 nm, allow their escape from the macrophage system and prolong their circulation 33 .…”
Section: Resultsmentioning
confidence: 99%